Best Answer

Yes, 3x and x are like terms because they have the same variable raised to the same power.

User Avatar

Wiki User

โˆ™ 2012-09-21 05:51:49
This answer is:
User Avatar
Study guides


20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

See all cards
818 Reviews

Add your answer:

Earn +20 pts
Q: Are 3x and x like terms?
Write your answer...
Still have questions?
magnify glass
Related questions

Combine like terms 3x plus x?

3x + x = 4x

Definition of like terms?

Like terms in mathematical problems are two variables that are the same. An example is 3x, x, 76x; because they all share x, they are like terms.

How do you simplify 3x-7-4-x?

Collect like terms together: 3x - 7 - 4 - x = (3x - x) + (-7 - 4) = (3 - 1)x + (-11) = 2x - 11

-x2 plus 3x equals -4?

-2x + 3x = -4 By combining like terms we get: x = -4.

What are the rules for combining like terms?

When combining like terms like 2x+3x we add their coeffitients, for example 2x+3x=(2+3)x=5x

What are similar terms?

They are terms that have the same variables like x, 2x and 3x or x2, 2x2 and 3x2

-3 plus 3x plus 6x equals 15?

-3 + 3x + 6x = 15 combine like terms 6x and 3x are like terms as are -3 and 15 9x = 18 x = 2

What are similar algebraic terms?

They are terms that have the same variables like x, 2x and 3x or x2, 2x2 and 3x2

Multiply (x - 6)(3x2 plus 10x - 1)?

Multiply each term of the second expression by each of the terms in the first expression and add them together, collecting like terms together: (x - 6)(3x² + 10x - 1) = x(3x² + 10x - 1) + (-6)(3x² + 10x - 1) = (3x³ + 10x² - x) + (-18x² - 60x + 6) = 3x³ + 10x² - 18x² - x - 60x + 6 = 3x² + (10 - 18)x² + (-1 - 60)x + 6 = 3x² - 8x² - 61x + 6

What is -3x-7 plus x-9 simpifed?

The expression reads as this: -3x-7+x-9 Combine like terms. -3x+x-7-9 -2x-16 If you would like to factor the expression, you can take out the coefficient -2, giving you -2(x+8).

How do you solve 6y-3x-9(1-1)?

6y-3x-9(1-1)=6y-3x-9(0)=6y-3x-0=6y-3xOnly like terms can be simplified. A like term has the same variables, X and Y are different variables. 6y-3x cannot be simplified because they are not like terms.

Combine like terms 5x plus x-9x?


People also asked